The Roles of WHO in Handling Yemen Humanitarian Crisis during the COVID-19 Pandemic - Andrini, Ghita Fadhila (UI Scholars Hub, 2021)
Yemen is noted to have the worst humanitarian crisis in the world. This condition is due to the civil war for the past six years, exacerbated by the COVID-19 pandemic, which emerged as a health security threat. This research aims to analyse the WHO’s role in responding health crisis in Yemen. By using qualitative methods and literature review approach, this article uses Atlas.ti to collect data regarding WHO’s activity in Yemen throughout the pandemic analysed by the international organisation’s role concept according to Clive Archer. The health security concept is also used to explain the health situation in Yemen during the pandemic. This research found accordance between WHO’s activities with Clive Archer’s idea of roles, mainly on its role as an independent actor to combat the health crisis in Yemen. However, the three roles are intertwined. As WHO has emphasised the importance of international aid to overcome Yemen’s health emergency, the writer recommends strengthening global solidarity with Yemen’s authority to improve health within the country.